2012
DOI: 10.1143/ptp.128.243
|View full text |Cite
|
Sign up to set email alerts
|

Negative Refraction with Little Loss Manipulated by the Voltage and Pulsed Laser in Double Quantum Dots

Abstract: The paper demonstrates that negative refractive index can be achieved via tuning the tunneling rate between a double quantum dots (QDs) system by applying a bias voltage, and a pulsed laser. As the bias voltage being changed, the refraction index can be tunable to negative with the simultaneous negative permittivity and permeability. While the varying pulsed laser is applied to the double QDs system, moreover, the negative refractive index with little loss can be obtained. The flexible manipulation on a solid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…A well-established route to constructing negative refractive index materials (NRMs) [1,2] is based on Veselago's theory of left-handed materials (LHM), simultaneous negative permittivity ( ) and magnetic permeability (µ) with different types of metamaterials. [3][4][5][6][7][8][9] Although very exciting from a physics point of view, the negative and µ produced by electromagnetic resonance may bring about a very highloss [10,11] and narrow bandwidth consequently. Due to the weaknesses of resonant-type structures, three groups almost simultaneously introduced a transmission line (TL) approach for NRM, [12][13][14][15] i.e., the composite right-left handed transmission line (CRLH-TL), which refers to the right-handedness accompanying the positive refraction index at high frequencies and to the lefthandedness with the negative refraction index (NRI) at lower frequencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A well-established route to constructing negative refractive index materials (NRMs) [1,2] is based on Veselago's theory of left-handed materials (LHM), simultaneous negative permittivity ( ) and magnetic permeability (µ) with different types of metamaterials. [3][4][5][6][7][8][9] Although very exciting from a physics point of view, the negative and µ produced by electromagnetic resonance may bring about a very highloss [10,11] and narrow bandwidth consequently. Due to the weaknesses of resonant-type structures, three groups almost simultaneously introduced a transmission line (TL) approach for NRM, [12][13][14][15] i.e., the composite right-left handed transmission line (CRLH-TL), which refers to the right-handedness accompanying the positive refraction index at high frequencies and to the lefthandedness with the negative refraction index (NRI) at lower frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…A well-established route for constructing negative refractive index materials (NRM) is based on Veselago's theory [1] of left-handed materials (LHM), simultaneous negative permittivity (ǫ) and magnetic permeability (µ) with different types of metamaterials [2][3][4][5][6][7]. Although very exciting from a physics point of view, the negative ǫ and µ produced by electromagnetic resonance may bring about a very high loss [8,9] and narrow bandwidth consequently.…”
mentioning
confidence: 99%
“…The tunable MMs are obviously very highly desired and potential expectations for future optical devices are, for example, spatial light modulators and tunable optical filters. There are various strategies reported for tuning the magnetic resonance of the permeability include electrical control [16,17], magnetically control [18], and temperature changing [19,20]. Generally, tunability is introduced by ferromagnetic materials [21,22], ferroelectric [13,23], liquid crystal [20,24,25], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The quantum coherence and interference has lead to many unforeseen investigations in multi-level atomic systems and semiconductor nanostructures due to their potential applications in quantum information technologies [20][21][22][23][24][25][26][27]. Semiconductor quantum dot (QD) nanostructures are very interesting nanoscale materials which have many natural benefits compared to atomic systems, such as high nonlinear optical coefficients and others.…”
Section: Introductionmentioning
confidence: 99%
“…The quantum coherence and interference in a QD structure can be induced by applying an intense laser field or by electron tunneling. It is shown that the negative refractive index can be achieved by tuning the tunneling rate between the double QD system via applying an external bias voltage, and an optical pumping light [21]. It is well known that variation in the refractive index of materials can manipulate the GH shifts in the reflected and transmitted light beams in a fixed cavity.…”
Section: Introductionmentioning
confidence: 99%